Study on Occupational Stress of Selected Public and Private Sector Banks in Erode District - M.Geethanjali; Dr. M.Hajerabanu (International Journal of Engineering and Management Research, 2023)
An individual's response to an upsetting environmental event is referred to as stress. Physical, psychological, and behavioural aberrations are the outcome of an organisational participant's adaptive reaction to an external event. Stress results from an imbalance between the difficulties faced and confidence in one's capacity to handle them. The difficulties can originate from outside forces and might be brought on by excessive or insufficient pressure. They could also originate from an individual's own internal value systems, wants, and expectations. Stress suggests some kind of pressure on the person, might be seen as a concern that it can lead to a psychological imbalance, and can undoubtedly have an impact on how well a person does. It is especially interested in how individuals adjust to changes in their personal, professional, and environmental conditions. The current research aims to evaluate the variables impacting the occupational stress of chosen employees of private and public sector banks in the Erode area.